1983
DOI: 10.1021/ja00352a016
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and excited triplet-state electron paramagnetic resonance of the .SIGMA.-bonded TCNQ dimer in bis(2,9-dimethyl-1,10-phenanthroline)copper(I) tetracyanoquinodimethane dimer [Cu(DMP)2]2[TCNQ]2

Abstract: Reaction of bis(2,9-dimethyl-1,10-phenanthroline)copper(I) iodide [Cu(DMP)2I] with lithium tetracyanoquinodimethanide, LiTCNQ, yields the compound [Cu(DMP)2]2[TCNQ]2, which crystallizes in the triclinic system, space group PI, with lattice parameters a = 12.784 A, b = 13.400 A, c = 12.136 k, a = 113.51°, ß = 112.58°, and 7 = 62.80°. The structure of the compound was solved by Fourier methods and refined by least-squares techniques to R = 0.060 on the basis of 1957 observed reflections. The structure consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 4 publications
2
25
0
Order By: Relevance
“…[6a, 11] Charge-transfer salt {[FeCp* 2 ] + } 2 [12] 2 2À (15): While exploring the ability of the TCNQ-derived acceptor 12 to form charge-transfer complexes with various electron donors, we found that the TCNQ moiety in 12 undergoes reductive s-dimerization upon reaction with the strong electron donor decamethylferrocene ([FeCp* 2 ]; E ox,1 = À0.59 V), [20] as previously observed for TCNQ. [33] Thus, an intense green solution was obtained upon addition of yellow [FeCp* 2 ] in CH 2 Cl 2 to the originally deeppurple solution of 12 in dry acetonitrile at 25 8C. The solid obtained after evaporation of the solvents was recrystallized by slow diffusion of n-hexane into CH 2 Cl 2 solution to afford dark-green crystals of {[FeCp* 2 ] + } 2 [12] A and B), four [FeCp* 2 ] + molecules, one of which is disordered, and three disordered CH 2 Cl 2 molecules ( Figure 6, for details, see the Experimental Section; for molecule B, see the Supporting Information).…”
Section: Slopementioning
confidence: 99%
“…[6a, 11] Charge-transfer salt {[FeCp* 2 ] + } 2 [12] 2 2À (15): While exploring the ability of the TCNQ-derived acceptor 12 to form charge-transfer complexes with various electron donors, we found that the TCNQ moiety in 12 undergoes reductive s-dimerization upon reaction with the strong electron donor decamethylferrocene ([FeCp* 2 ]; E ox,1 = À0.59 V), [20] as previously observed for TCNQ. [33] Thus, an intense green solution was obtained upon addition of yellow [FeCp* 2 ] in CH 2 Cl 2 to the originally deeppurple solution of 12 in dry acetonitrile at 25 8C. The solid obtained after evaporation of the solvents was recrystallized by slow diffusion of n-hexane into CH 2 Cl 2 solution to afford dark-green crystals of {[FeCp* 2 ] + } 2 [12] A and B), four [FeCp* 2 ] + molecules, one of which is disordered, and three disordered CH 2 Cl 2 molecules ( Figure 6, for details, see the Experimental Section; for molecule B, see the Supporting Information).…”
Section: Slopementioning
confidence: 99%
“…Solid state conductivities of 2 and 3 at room temperature are of the order of 10 À10 S cm À1 , indicating that the complexes are weak conductors. This may be attributed to structural arrangements of TCNQ species in the complexes [23].…”
Section: Resultsmentioning
confidence: 99%
“…. [24][25][26][27] Notably, the small   1 of about 94° and the   2 bond angle of 100° exist in these one-sided molecules and in the graphitic Y junctions [28]. For stability, although small bond angles   1 and   2 are unfavorable (  1 and   2 may be improved by changing the sizes of the cage and the bridge), the formed single bonds R2 and R3 are favorable factors.…”
Section: Geometrical Characteristicsmentioning
confidence: 99%